2015
DOI: 10.1200/jco.2015.33.3_suppl.770
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of 5-fluorouracil (5FU) dose by pharmacokinetic (PK) monitoring in Asian patients with advanced-stage gastrointestinal (GI) cancer.

Abstract: 770 Background: PK guided dose management and systemic plasma levels of 5FU have shown correlation with both reduced toxicity and improved efficacy. However, data for Asian patients are lacking. Levels are highly variable with doses based on body surface area. Methods: Area under the curve (AUC) was estimated using a nanoparticle immunoassay from Saladax Biomedical (My5-FU). Patients with GI cancers receiving de Gramont, FOLFIRI or mFOLFOX6 regimens had 5 PK sampling time points obtained (reduced to 2 samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Only a single conference abstract failed to show such effects from TDM of 5-FU. 85 Is there evidence that TDM reduces toxicity in patients receiving 5-FU?…”
Section: Evaluation Of Tdmmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a single conference abstract failed to show such effects from TDM of 5-FU. 85 Is there evidence that TDM reduces toxicity in patients receiving 5-FU?…”
Section: Evaluation Of Tdmmentioning
confidence: 99%
“…4 However, this AUC target has only an $20% range, which is rather small, especially given the significant intrapatient variability and reported commercial testing experience, potentially resulting in frequent unnecessary dose adjustments. 30 Based on subsequent observational clinical studies and a review of the PK-PD data, the target range was subsequently widened to 20-30 mgÁh/L, and applied to 46-hour infusion schedules of 5-FU, as is now typically used with modern chemotherapy regimens, such as FOLFOX6 or FOLFIRI 16,30,33,85,100 (see also Figure 1). The recommended exposure target range of 20-30 mgÁh/L is not appropriate for 5-FU bolus dosing and infusions of 120 hours and longer.…”
Section: Are Reliable Assays Available?mentioning
confidence: 99%
See 1 more Smart Citation
“…Soh et al reported on the clinical experience with PK-guided dose adjustment of 5-FU in Asian patients (N = 50) with GI cancers (CRC in 76% and gastric cancer in 12%) receiving LV5FU2 (2%), FOLFIRI (36%), or mFOLFOX6 (62%) chemotherapy [40]. Plasma 5-FU AUC values were determined using an immunoassay, and 5-FU dose adjustments were recommended using a target 5-FU AUC of 18–28 mg•35;h/L.…”
Section: Prospective Pk-based Dose Adjustment With Clinical Evaluationmentioning
confidence: 99%
“…When patients frequently cannot receive therapy because of considerable financial burden labeled as “financial toxicity,” cost-effectiveness has now become an even more crucial factor to take into account. There are two studies [conducted by Goldstein (2014) and Soh (2015)] that evaluated the cost-effectiveness of TDM, and it has been observed that 5-FU TDM is economical in the management of both mCRC and SCCHN ( 104 , 105 ). Associated toxicities with 5-FU, such as febrile neutropenia, nausea/vomiting, and diarrhea, can have serious negative clinical and cost effects on patients and the healthcare system.…”
Section: Fluorouracilmentioning
confidence: 99%